2021
DOI: 10.2147/ijgm.s323579
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Uric Acid and Insulin-Like Growth Factor-1 in Type 2 Diabetes Mellitus

Abstract: Objective: This research examined the relationship between uric acid (UA) and insulin-like growth factor-1 (IGF-1) in patients with type 2 diabetes mellitus (T2DM). Methods: This study was a cross-sectional study that included 1230 Chinese patients with T2DM. We collected general information and laboratory indicators and calculated the standard deviation score of IGF-1 (IGF-1 SDS). Results:The univariate analysis results demonstrated a significant positive relationship between UA levels and IGF-1 SDS (P<0.001)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…[ 14 ] This condition is implicated in the underlying mechanism of hyperuricemia and the occurrence of diabetes, and it plays a crucial role in the pathogenesis of diabetes. [ 8 50 51 52 53 54 55 ] This finding supports the hypothesis that serum UA might be involved in the early stages of impaired glucose metabolism leading to prediabetes and accelerating the development of diabetes.…”
Section: Discussionsupporting
confidence: 75%
“…[ 14 ] This condition is implicated in the underlying mechanism of hyperuricemia and the occurrence of diabetes, and it plays a crucial role in the pathogenesis of diabetes. [ 8 50 51 52 53 54 55 ] This finding supports the hypothesis that serum UA might be involved in the early stages of impaired glucose metabolism leading to prediabetes and accelerating the development of diabetes.…”
Section: Discussionsupporting
confidence: 75%
“…However, we did not find a causal effect of serum urate on the markers of systematic inflammation. Previous studies have observed the associations between serum urate and serum inflammation indicators ( 13 , 61 , 62 ). Our study indicates that these associations are not causal.…”
Section: Discussionmentioning
confidence: 95%
“…Negative and nonlinear correlations between IGF-1 and UA levels have however been reported in nondiabetic and T2DM adults. 66,67 IGF-1 also inhibits secretion of insulin, 6 and insulin reduces renal fractional excretion of urate [68][69][70] by stimulating urate transport through GLUT9a and other reabsorptive urate transporters. 65 We hypothesized that IGF-1 also exerts direct effects on urate transport mechanisms.…”
Section: Discussionmentioning
confidence: 99%